(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this paper I analyze a conflict between the Comisión Provincial por la Memoria (CPM) (institution where the archive of the Dirección de Inteligencia de la Provincia de Buenos Aires works), and the human rights organization Hijos por la Identidad y la Justicia contra el Olvido y el Silencio (HIJOS), at that time composed mainly by children of victims of State terrorism. In 2005, the CPM held a call for hiring workers to the archive. The intention was to give a “professional” bias to the institution in general and to the particular archive. Several members of the HIJOS group were part of that call, who understood that they carried enough legitimacy to be part of the institution. Here I explore the crossing between a logic based on the legitimacy of the blood ties with another based on “transparency” and “professionalization”.